Designing and developing instructional recorded demonstration models for non-English speaking learners - Ansyari, Muhammad Fauzan (Journal of English and Arabic Language Teaching, 2012)
This report used a design research approach that was aimed to redesign instructional videos for procedures. This project incorporated the minimalism theory, the four components model principles, multimedia learning principles, and recorded demonstration principles as the foundational frameworks.There were three phases undertaken to achieve such purpose. In phase one, the existing Camtasia Studio 7 video series were analysed and relevant theoretical foundations for instructional videos were examined. Both were used to further guide the design or development of the prototypes. Design guidelines were then generated from the analyses and theories. In phase two, the initial prototype was constructed and tested with target users. In final phase, the effectiveness of the revised model is retested and formatively re-evaluated.The results revealed that the above-mentioned theories, principles, and guidelines are vital in the design of an effective, efficient, and appealing instruction for users’ performance and support. In other words, an outright violation of those theories, guidelines, and principles can seriously jeopardize the effectiveness of a recorded instructional video for procedures.